Mixed-scale poly(methyl methacrylate) channel network-based single-particle manipulation via diffusiophoresis. Issue 30 (25th May 2018) - Hong, Jisoo; Kim, Beomsang; Shin, Heungjoo
Abstract : Simple and controllable single-particle manipulation via diffusiophoresis was demonstrated using a mixed-scale PMMA channel network including 3D microfunnels working as chambers. Abstract : Despite the unique advantages of nanochannels imparted by their small size, their utility is limited by the lack of affordable and versatile fabrication methods. Moreover, nanochannel-incorporated fluidic devices require micro-sized conduit integration for efficient access of liquid samples. In this study, a simple and cost-effective fabrication method for mixed-scale channel networks via hot-embossing of poly(methyl methacrylate) (PMMA) using a carbon stamp is demonstrated. Due to its high rigidity, PMMA ensures collapse-free channel fabrication. The carbon stamp is fabricated using only batch microfabrication and has a convex architecture that allows the fabrication of a complex channel network via a single imprinting process. In addition, the microchannels are connected to nanochannels via three-dimensional (3D) microfunnels that serve as single-particle-entrapment chambers, ensuring smooth transport of samples into the nanochannels. Owing to the 3D geometry of the microfunnels and the small size of the nanochannels, a solute gradient can be generated locally at the microfunnel. This local solute gradient enables the entrapment of microparticles at the microfunnels via diffusiophoresis, which can manipulate the particle motion in a controllable manner, without any external equipment or additional electrode integration into the channels. To the best of our knowledge, this is the first report of diffusiophoresis-based single-particle entrapment.